Python deep learning : next generation techniques to revolutionize computer vision, AI, speech and data analysis /: next generation techniques to revolutionize computer vision, AI, speech and data analysis. (2017) - Zocca, Valentino; Spacagna, Gianmario; Slater, Daniel; Roelants, Peter
No abstract available